2004
DOI: 10.1100/tsw.2004.195
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Health Effects of Long-Term Exposure to Insecticide-Treated Mosquito Nets in the Control of Malaria in Endemic Regions

Abstract: Malaria is a protozoan disease caused in humans by the genusAll pesticides are toxic by nature and present risks of adverse effects that depend on toxicity of the chemical and the degree of exposure. While there is agreement that ITMNs can be effective in reducing malaria morbidity and mortality under field trials, a number of factors relating to their sustainability and contribution to health improvement in lessdeveloped countries have yet to be determined. In particular, the adverse effects associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In order to avoid the need for periodic self re-treatment of ITNs which, simultaneously, reduces the overall insecticide exposure risk to the user (Anyanwu et al 2006;Sharma et al 2009), one of the most beneficial antimalarial strategies developed in recent years has been the implementation of factory-treated long-lasting treated nets (LLINs) (N'Guessan et al 2001). Although LLINs result in higher wash-resistance and residual activity thus maintaining insecticidal and, therefore, protective efficacy (WHO 2005), a significant loss of insecticide concentration and efficacy has been reported after both hand-and machine-laundering methods (N'Guessan et al 2001;Ordonez Gonzalez et al 2002;Sharma et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid the need for periodic self re-treatment of ITNs which, simultaneously, reduces the overall insecticide exposure risk to the user (Anyanwu et al 2006;Sharma et al 2009), one of the most beneficial antimalarial strategies developed in recent years has been the implementation of factory-treated long-lasting treated nets (LLINs) (N'Guessan et al 2001). Although LLINs result in higher wash-resistance and residual activity thus maintaining insecticidal and, therefore, protective efficacy (WHO 2005), a significant loss of insecticide concentration and efficacy has been reported after both hand-and machine-laundering methods (N'Guessan et al 2001;Ordonez Gonzalez et al 2002;Sharma et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While there is no doubt about the effectiveness of ITNs and the main challenge now is to scale up their use (WHO, 2002). Review reports on the benefits of ITNs did not yield any information relating to the potential adverse effects of long-term exposure to insecticide treated products (Anyanwu et al, 2006). However, Kolaczinski and Curtis (2004) concluded that chronic effects can presently not be excluded with certainty, as relevant toxicological data do not exist in the open scientific literature.…”
Section: Hazard Of Pyrethroids Insecticides Use For Itns and Irsmentioning
confidence: 99%
“…While there is agreement that ITNs can be effective in reducing malaria morbidity and mortality under field trials, the adverse effects associated with their use at different level of age groups and sex has not yet to be fully evaluated. Some scientists raised concerns about the long-term effects of ITNs exposures, especially on children and pregnant women (Anyanwu et al, 2004). In their comprehensive literature review, Anyanwu et al (2006) show that not much work has been done on the effects of long-term exposure to ITNs.…”
Section: Hazard Of Pyrethroids Insecticides Use For Itns and Irsmentioning
confidence: 99%
See 2 more Smart Citations